Strategie a techniky kontroly znečištění pro spalovací procesy - Kunc, Vlastimil (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Bakalářská práce se zabývá problematikou spalovacích procesů. V práci je uveden přehled a popis jednotlivých konstrukčních parametrů spalovacího zařízení a jejich vlivu na tvorbu emisí. Práce dále popisuje jednotlivé druhy emisí vznikajících při spalování, jejich vliv na životní prostředí a techniky používané pro jejich redukci. Práci uzavírá kapitola s přehledem emisních limitů v ČR.

Bachelor’s thesis deals with the problems of combustion process. The work gives the overview and the description of individual design parameters of the combustion facility. The analysis of the influence of design parameters on emissions formation is followed by the description of individual kinds of emissions and their impact on the environment. Next the most used reduction techniques are described. The work is closed by the overview of the emission limits in the Czech Republic.
Pollution control strategies and techniques for combustion processes
Keywords: Emise; životní prostředí; redukční techniky; spalovací proces; Emissions; environment; reduction techniques; combustion process